Efeito da carbonatação acelerada em compósitos de fibrocimento extrudados com resíduo de quartzito e fibras de coco - Pereira, Tamires Galvão Tavares (2021)
Brazil is worldwide known for its production and commercialization of ornamental rocks that correspond to 5.6% of participation in the international market of processed rocks, reaching the production of 9.2 million tons in 2019. However, the processing of ornamental rocks generates approximately 3,260,000 tons of residue in Brazil, causing severe environmental impacts. Therefore, this study aimed to evaluate the incorporation of different percentages of quartzite residue (0, 25, 50, 75, and 100%) in the production of extruded fiber-cement composites reinforced with coconut fiber, as well as to analyze the impact of exposure to different accelerated carbonation times in the physical and mechanical properties of the composites. For the production of the composites, Portland cement CPV-ARI, agricultural limestone, and 2% (by mass) of Cocos nucifera fibers were used. Hydroxypropylmethylcellulose (HPMC) and carboxylic polyester (ADVA) were added as additives. The water/cement ratio (by mass) was approximately 0.40. The specimens were made by the extrusion process and remained 28 days in the curing process in a saturated environment. The addition of quartzite residue increased the values of apparent density (DA) and apparent porosity (PA), leading to lower water absorption (AA) of the composites for all treatments. Consequently, there was a positive increase in the mechanical properties of modulus of rupture (MOR), limit of proportionality (LOP), and toughness. Subsequently, composites with 100% quartzite were subjected to the accelerated carbonation process (0, 6, 12, and 24 h). There was no statistically significant difference between the apparent density of composites exposed to different carbonation times; however, it reduced the apparent porosity by up to 6% in 12 h of exposure. Water absorption reduced 8.74% with 6 h of carbonation. Regarding the MOR, modulus of elasticity (MOE), and LOP, there was no statistical difference among the non-carbonated composites (control) and those that underwent accelerated carbonation at different times. Toughness increased from 2.18 (control) to 3.69 KJ/m² for fiber-cement composites exposed to 12 h of carbonation, a 69.26% increase. The study demonstrated that the use of quartzite residues and coconut fibers, as well as the accelerated carbonation of the fiber-cement, have great potential for the production of lighter, tougher, and more sustainable materials.